Is Dementia-Specific Caregiving Compared With Non-Dementia Caregiving Associated With Physical Difficulty Among Caregivers for Community-Dwelling Adults?. (April 2022) - Parker, Lauren J.; Fabius, Chanee; Rivers, Emerald; Taylor, Janiece L.
Objective: The purpose of this study is to identify whether dementia caregiving is associated with physical difficulty among informal caregivers. Methods: This cross-sectional retrospective cohort study design used data from the 2015 National Health and Aging Trends Study and the National Study of Caregiving. Binary logistic regression was used to examine the association between substantial physical difficulty and dementia caregiving among 1, 871 caregivers. Results: Nearly 14% of the caregivers reported substantial physical difficulty. Dementia caregivers were 1.5 times more likely to report caregiving-related substantial physical difficulty (adjusted odds ratio [AOR] = 1.58, p = .04) than non-dementia caregivers. Factors associated with substantial physical difficulty included caregiver gender, self-rated health, depressive symptoms, pain, and caring for someone receiving assistance with three or more self-care or mobility activities. Discussion: Future studies should identify strategies to mitigate the physical demands on dementia caregivers. Early monitoring of caregivers' self-rated health, depressive symptoms, and pain may identify those more likely to experience physical difficulty.